PERAN PPNS DALAM PENEGAKAN HUKUM TERHADAP PELANGGARAN TINDAK PIDANA RINGAN DI KABUPATEN SLEMAN - Wantara Wantara; Hartanto Hartanto; Kelik Endro Suryono (Musamus University, 2020)
The problems examined in this study are based on problems that occur in the storage, distribution, and sale of alcoholic beverages and the prohibition of unlicensed mixed drinks in the Sleman Regency area. Even though the Sleman Regency Government has just Regulated the Regional Regulation of Sleman Regency Number 8 Year 2019 regarding Control and Supervision of Alcoholic Beverages and Prohibition of Mixed Beverages. This study is to determine the role and constraints of Civil Servants' Discipline in law enforcement against violations of the law reaching the Court. The study was conducted with empirical juridical research methods. The results showed that the only regional apparatus that was authorized to enforce the Regional Regulation was the Sleman District Civil Service Police Unit, whereas for law enforcement against criminal offenses the authorities other than the National Police Investigators were the Civil Servant Investigators (PPNS). PPNS actions in handling this case refer to the Criminal Procedure Code and in its filing use the Quick Examination Program which is intended for Light Criminal Acts (Tipiring) Keywords: Violation, Regional Regulation, Beverage, Alcoholic